Advances in Microbial Genome Reduction and Optimization Based on Synthetic Biology - Tianli SUN; Mingzhu HUANG; Bin LIU; Xuelan CHEN (Shipin gongye ke-ji)
The engineering and optimization of microbial strains form the core of modern industrial biotechnology, and the foundation of industrial microbial chassis cells has emerged as a hotspot in the field of synthetic biology. Guided by the "design-build-test-learn" approach, designing and engineering microbial chassis cells have become the critical strategy to develop excellent cell factories. This study presents a comprehensive review on strategies for modification and optimization of microbial chassis cells in synthetic biology. Meanwhile, this study summarized the applications and platforms benefited from industrial microbial chassis cells based on biology synthesis. Finally, this study discussed challenges encountered during chassis cell construction and put forward the future prospects to pave the way for microbial cell factories with superior attributes.